Preeclampsia: From Cellular Wellness to Inappropriate Cell Death, and the Roles of Nutrition - Angga Wiratama Lokeswara (Frontiers Media S.A., 2021)
Preeclampsia is one of the most common obstetrical complications worldwide. The pathomechanism of this disease begins with abnormal placentation in early pregnancy, which is associated with inappropriate decidualization, vasculogenesis, angiogenesis, and spiral artery remodeling, leading to endothelial dysfunction. In these processes, appropriate cellular deaths have been proposed to play a pivotal role, including apoptosis and autophagy. The proper functioning of these physiological cell deaths for placentation depends on the wellbeing of the trophoblasts, affected by the structural and functional integrity of each cellular component including the cell membrane, mitochondria, endoplasmic reticulum, genetics, and epigenetics. This cellular wellness, which includes optimal cellular integrity and function, is heavily influenced by nutritional adequacy. In contrast, nutritional deficiencies may result in the alteration of plasma membrane, mitochondrial dysfunction, endoplasmic reticulum stress, and changes in gene expression, DNA methylation, and miRNA expression, as well as weakened defense against environmental contaminants, hence inducing a series of inappropriate cellular deaths such as abnormal apoptosis and necrosis, and autophagy dysfunction and resulting in abnormal trophoblast invasion. Despite their inherent connection, the currently available studies examined the functions of each organelle, the cellular death mechanisms and the nutrition involved, both physiologically in the placenta and in preeclampsia, separately. Therefore, this review aims to comprehensively discuss the relationship between each organelle in maintaining the physiological cell death mechanisms and the nutrition involved, and the interconnection between the disruptions in the cellular organelles and inappropriate cell death mechanisms, resulting in poor trophoblast invasion and differentiation, as seen in preeclampsia.